Durability of the efficacy and safety of alogliptin compared with glipizide in type 2 diabetes mellitus: a 2‐year study1. Issue 12 (25th September 2014) - Del Prato, S.; Camisasca, R.; Wilson, C.; Fleck, P.
<x xml:space="preserve">Abstract</x> Aims To evaluate the long‐term durability of the efficacy of alogliptin compared with glipizide in combination with metformin in people with type 2 diabetes inadequately controlled on stable‐dose metformin. Methods This multicentre, double‐blind, active‐controlled study randomized 2639 patients aged 18–80 years to 104 weeks of treatment with metformin in addition to alogliptin 12.5 mg once daily (n = 880), alogliptin 25 mg once daily (n = 885) or glipizide 5 mg once daily, titrated to a maximum of 20 mg (n = 874). The primary endpoint was least square mean change from baseline in HbA1c level at 104 weeks. Results The mean patient age was 55.4 years, the mean diabetes duration was 5.5 years and the mean baseline HbA1c was 7.6%. HbA1c reductions at week 104 were −0.68%, −0.72% and −0.59% for alogliptin 12.5 and 25 mg and glipizide, respectively [both doses met the criteria for non‐inferiority to glipizide (p<0.001); alogliptin 25 mg met superiority criteria (p=0.010)]. Fasting plasma glucose concentration decreased by 0.05 and 0.18 mmol/l for alogliptin 12.5 and 25 mg, respectively, and increased by 0.30 mmol/l for glipizide (p < 0.001 for both comparisons with glipizide). Mean weight changes were −0.68, −0.89 and 0.95 kg for alogliptin 12.5 and 25 mg and glipizide, respectively (p < 0.001 for both comparisons with glipizide). Hypoglycaemia occurred in 23.2% of patients in the glipizide group vs. 2.5 and 1.4% of patients in the alogliptin 12.5 and 25 mg groups, respectively. Pancreatitis occurred in one patient in the alogliptin 25 mg group and three in the glipizide group. Conclusions Alogliptin efficacy was sustained over 2 years in patients with inadequate glycaemic control on metformin alone.